Stationary Mode and Binomial Moments for Networks of the Type [SM|GI|∞]^r - Lebedev, E. O. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
By using methods of the Markov renewal theory, we find conditions for the existence of a stationary mode for multichannel networks with semi-Markov input stream. As a tool of stationary distribution analysis, we introduce multivariate binomial moments and investigate their asymptotic properties. For a multichannel queuing system with periodic input stream, we construct the generating function of the stationary distribution in explicit form in terms of the parameters of the system under consideration.